A Critical Evaluation of the Estonian Cyber Incident - Buresh, Donald L. (Journal of Advanced Forensic Sciences, 2020)
This paper evaluates the effect of the Estonian cyber incident on Estonia, Russia, the United States, the European Union, and the North Atlantic Treaty Organization, also known as NATO. The paper employs the Valeriano and Maness criteria for evaluating a cyber incident critically. The article asks how did the Estonian cyber incident come to pass, what were the foreign policy and international relationship effects, what was the impact on Estonia, and how did Estonia react to the attack. The essay concludes that the Estonian cyber incident was a catalyst, prompting the nations listed herein to address the effects of cyber-attacks, and then search for acceptable solutions.
Keywords: Cyber-attack; Cyber terrorism; Digital terrorism; Estonian cyber-attack